1986
DOI: 10.1530/acta.0.1130396
|View full text |Cite
|
Sign up to set email alerts
|

Steroidogenic activity of highly potent melanotropic peptides in the adrenal cortex of the rat

Abstract: Highly purified ACTH and MSH peptides were studied in isolated rat glomerulosa and inner zone cells and their activity compared with that in an Anolis melanophore assay. While both ACTH1-39 and ACTH1-24 were almost equally potent steroidogenic peptides in the two cell types (ED50 between 1 and 4 \ m=x\ 10\m=-\12 m), \g=a\-MSHdisplayed only weak steroidogenic activity. Although it was a full agonist, it was about 104-fold less potent in both capsular and inner zone cells. \g=b\-MSH(porcine) was even 10-fold les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…To ensure that this effect represented a true initiation of a secretory response, rather than the amplification of a glucose-induced secretory response (see Ashcroft & Ashcroft 1992), in these experiments the basal glucose concentration was maintained at 2 mM, well below the threshold at which glucose will initiate a secretory response (4-5 mM; Ashcroft & Ashcroft 1992). The naturally occurring hormone, ACTH 1-39 , and a synthetic peptide with full corticotropic activity, ACTH 1-24 (Baumann et al 1986), were similarly effective as insulin secretagogues in static incubations over doses ranging from 100 pM to 10 nM. In perifusion experiments using MIN6 cells configured as pseudoislets, the response to 1 and 10 nM ACTH at 2 mM glucose was characterized by a rapid increase in insulin secretion that returned to almost basal levels within 15 min in the continued presence of the peptide.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure that this effect represented a true initiation of a secretory response, rather than the amplification of a glucose-induced secretory response (see Ashcroft & Ashcroft 1992), in these experiments the basal glucose concentration was maintained at 2 mM, well below the threshold at which glucose will initiate a secretory response (4-5 mM; Ashcroft & Ashcroft 1992). The naturally occurring hormone, ACTH 1-39 , and a synthetic peptide with full corticotropic activity, ACTH 1-24 (Baumann et al 1986), were similarly effective as insulin secretagogues in static incubations over doses ranging from 100 pM to 10 nM. In perifusion experiments using MIN6 cells configured as pseudoislets, the response to 1 and 10 nM ACTH at 2 mM glucose was characterized by a rapid increase in insulin secretion that returned to almost basal levels within 15 min in the continued presence of the peptide.…”
Section: Discussionmentioning
confidence: 99%
“…MC2R is acknowledged only to be activated by ACTH (Baumann et al 1986), for which reason binding studies were not performed on this receptor. In order to assess MCR agonist specificity, competition binding curves of ACTH, -MSH, NDP--MSH, MT-II, PG-901, SHU9119 and LY2112688 were obtained using cells over-expressing murine MC1R (mouse melanoma cells), murine MC3R and MC5R (recombinant CHO-K1 cells) and murine MC4R (recombinant BHK570 cells) (table 1).…”
Section: Binding Studiesmentioning
confidence: 99%
“…These peptides are generated from a common precursor proopiomelanocortin (POMC) and function as MCR agonists. It has previously been shown, that MC2R binds ACTH and none of the other POMC derived peptides (Baumann et al 1986;Boston & Cone 1996). When a MCR is stimulated, it couples to G s , which activates intracellular adenylyl cyclase and increases cAMP production.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent investigations have shown an increase in anterior lobe content of IR-a-MSH in rat pituitaries following adrenalectomy (Estivariz et al, 1988). Desacetyl-a-MSH has also been shown to be a full agonist of a-MSH in stimulating the rat adrenal cortex (Baumann et al, 1986). Desacetyl-a-MSH has also been shown to be a full agonist of a-MSH in stimulating the rat adrenal cortex (Baumann et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The function of a-MSH in mammals is largely unknown, although recent work has concentrated on its stimulation of the zona glomerulosa (Vinson et al, 1980). Thus, it has been repeatedly shown that a-MSH stimulates release of aldosterone in vitro from the rat adrenal (Szalay & Stark, 1982;Vinson et al, 1983Vinson et al, , 1986Baumann et al, 1986). Experiments performed in vivo have also demonstrated the specific steroidogenic action of a-MSH (Shenker et al, 1985) and in addition have suggested that a-MSH is mitogenic to cells of the rat zona glomerulosa (Robba et al, 1986).…”
mentioning
confidence: 99%